Siravyadhana in Parivartika – A scientific review - Chakraborty, Sayantan; Kundu, Debasis; Nayak, Leena (International Research Journal of Ayurveda & Yoga, 2021)
Parivartika or paraphimosis is a very painful emergency condition. Here vitiation of Vyanvayu at Medra Charma (prepucial skin) that is why circulation of penis hampered. And then gradually Kapha And Pitta vitiation may occur and symptoms like Kandu (Itching), Daha (burning sensation), Paka, Sotha (inflammation) appears. The Siravyadhana releases the polluted Vyan Vayu as well as Pitta and Kapha that’s why Acharya Sushruta advocated this minimum invasive procedure. In modern science dorsal slit or multiple puncturing is done to reduce oedema which creates more exposure to infections. By seeing these two Sira Vyadhana (single minimum invasion) can be effective in case of Parivartika